Bone marrow- or adipose-mesenchymal stromal cell secretome preserves myocardial transcriptome profile and ameliorates cardiac damage following ex vivo cold storage. (March 2022) - Scott, Susan R.; March, Keith L.; Wang, I-Wen; Singh, Kanhaiya; Liu, Jianyun; Turrentine, Mark; Sen, Chandan K.; Wang, Meijing
Abstract: Background: Heart transplantation, a life-saving approach for patients with end-stage heart disease, is limited by shortage of donor organs. While prolonged storage provides more organs, it increases the extent of ischemia. Therefore, we seek to understand molecular mechanisms underlying pathophysiological changes of donor hearts during prolonged storage. Additionally, considering mesenchymal stromal cell (MSC)-derived paracrine protection, we aim to test if MSC secretome preserves myocardial transcriptome profile and whether MSC secretome from a certain source provides the optimal protection in donor hearts during cold storage. Methods and results: Isolated mouse hearts were divided into: no cold storage (control), 6 h cold storage (6 h-I), 6 h-I + conditioned media from bone marrow MSCs (BM-MSC CM), and 6 h-I + adipose-MSC CM (Ad-MSC CM). Deep RNA sequencing analysis revealed that compared to control, 6 h-I led to 266 differentially expressed genes, many of which were implicated in modulating mitochondrial performance, oxidative stress response, myocardial function, and apoptosis. BM-MSC CM and Ad-MSC CM restored these gene expression towards control. They also improved 6 h-I-induced myocardial functional depression, reduced inflammatory cytokine production, decreased apoptosis, and reduced myocardial H2 O2 . However, neither MSC-exosomes nor exosome-depleted CM recapitulated MSC CM-ameliorated apoptosis and CM-improved mitochondrial preservation during cold ischemia. Knockdown of Per2 by specific siRNA abolished MSC CM-mediated these protective effects in cardiomyocytes following 6 h cold storage. Conclusions: Our results demonstrated that using MSC secretome (BM-MSCs and Ad-MSCs) during prolonged cold storage confers preservation of the normal transcriptional "fingerprint", and reduces donor heart damage. MSC-released soluble factors and exosomes may synergistically act for donor heart protection. Graphical abstract: Unlabelled Image Highlights: MSC secretome preserves normal transcriptional profiling in hearts with cold storage. MSC's origin is not a key determinant for MSC secretome-derived protective effect. MSC-trophic factors and exosomes synergistically act for donor heart preservation. Knockdown of Per2 abolishes MSC secretome-mediated protective activity in myocytes.